Biodiesel production from lipid of carbon dioxide sequestrating bacterium and lipase of psychrotolerant Pseudomonas sp. ISTPL3 immobilized on biochar. (December 2017) - Khosla, Khushboo; Rathour, Rashmi; Maurya, Raj; Maheshwari, Neha; Gnansounou, Edgard; Larroche, Christian; Thakur, Indu Shekhar
Highlights: Lipase producing psychrotolerant bacterium identified as Pseudomonas sp. ISTPL3. Lipase was alkalophilc, thermostable, active in organic solvents and sensitive detergents. Immobilized lipase gave high FAME yield in biodiesel produced. Reusability of immobilized lipase was established. Abstract: An extracellular lipase was purified and characterized from psychrotolerant bacterium Pseudomonas sp. ISTPL3 isolated from Pangong lake. Lipase was purified by sequential methods of ammonium sulphate precipitation, dialysis, DEAE-cellulose ion exchange chromatography and Sephadex G-100 gel filtration chromatography, resulting in a purification fold of 6.53 and yield of 5.45%. The molecular weight was approximately 31 kDa. The purified lipase was used for transesterification of lipids produced by oleaginous chemolithotrophic bacterium Serratia sp. ISTD04 for production of biodiesel. Upon biochemical characterization, lipase was found to be alkalophilc, thermostable, active in organic polar solvents and sensitive to detergents. Further, lipase was immobilized on activated biochar to assess its transesterification efficiency during biodiesel production. Immobilized lipase gave the highest yield of fatty acid methyl esters (FAMEs) (92.23%) > unimmobilized lipase > NaOH. The immobilized lipase was assessed for its reusability and retained 75.11% of its activity after 3 cycles of biodiesel production.